2023
DOI: 10.1259/bjr.20230211
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence (AI) and machine learning (ML) in precision oncology: a review on enhancing discoverability through multiomics integration

Lise Wei,
Dipesh Niraula,
Evan D H Gates
et al.

Abstract: Multiomics data including imaging radiomics and various types of molecular biomarkers have been increasingly investigated for better diagnosis and therapy in the era of precision oncology. Artificial intelligence (AI) including machine learning (ML) and deep learning (DL) techniques combined with the exponential growth of multiomics data may have great potential to revolutionize cancer subtyping, risk stratification, prognostication, prediction and clinical decision-making. In this article, we first present d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 99 publications
(99 reference statements)
0
10
0
Order By: Relevance
“…Indeed, multiple studies have shown that unsupervised learning approaches applied to a combination of clinical, genetic, and imaging data can identify novel distinct—and likely more inclusive—phenotypes of disease that can serve to improve predictions of both disease outcomes and their responses to interventions. 58…”
Section: Bias In Medicine and Mitigation By MLmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, multiple studies have shown that unsupervised learning approaches applied to a combination of clinical, genetic, and imaging data can identify novel distinct—and likely more inclusive—phenotypes of disease that can serve to improve predictions of both disease outcomes and their responses to interventions. 58…”
Section: Bias In Medicine and Mitigation By MLmentioning
confidence: 99%
“…While extending the benefits of radiomics, which generates imaging biomarkers of disease, AI methods also offer benefits to multisource data including genetic, epigenetic, transcriptomic, proteomic, metabolomic, and other types of molecular biomarker data. As recommended by experts in cardiovascular imaging, as well as other fields, 57,58 the contributions of AI methods applied to multiomics data are at least 2-fold. First, AI methods add new computational capabilities for harnessing vast amounts of high-dimensional data and analyzing their complex inter relations.…”
Section: Facilitating Interpretation By Computer Vision Image Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of novel cancer therapies 1,2 and increasing availability of longitudinal multi-omics data 3,4 have improved our ability to prescribe personalized, adaptive treatment strategies [5][6][7] capable of dynamically reacting to individual cancer progression while improving efficacy and minimizing side effects. However, the dynamic nature of adaptive strategies compounded by a wide range of clinical options, high data dimensionality, uncertainty in assessing treatment response, and the uncertainty in the future course of disease, present challenges in tailoring optimal strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted with the aim of elucidating the experiences of cancer survivors with healthcare systems in five European nations. In the current milieu of precision oncology, there has been a growing emphasis on multi-omics data, encompassing imaging radiomics and diverse molecular biomarkers, to refine diagnostic and therapeutic approaches ( 14 ). The integration of AI, encompassing machine learning (ML) and deep learning (DL), with the expanding accumulation of multi-omics data, holds considerable promise to bring transformative changes in areas such as cancer subtyping, risk stratification, prognostic evaluations, predictive analytics, and clinical decision-making processes ( 14 ).…”
mentioning
confidence: 99%